Mesozoic palaeomagnetism in Vestfjella, Dronning Maud Land, East Antarctica - Løvlie, Reidar (Geophysical Journal International, 1979)
Thermal and alternating field demagnetization of oriented samples of Mesozoic lava flows (200–230 Myr) and dykes (154–172 Myr) collected from seven nunataks within the Vestfjella region, Dronning Maud Land, revealed stable directions of magnetization of normal and reverse polarity. Directional distributions of both polarities define tight groups along the same palaeomagnetic axis. Depending on whether the regional westward dip of the lava flows originated prior to, or after the intrusive igneous phase, two or one, respectively, palaeomagnetic pole(s) can be estimated. Both poles, however, are in general accord with previous Mesozoic poles from East Antarctica.